EFEKTIVITAS STRATEGI DINAS PERDAGANGAN DALAM PENGEMBANGAN INDUSTRI KECIL BATIK DI KABUPATEN KEDIRI PROVINSI JAWA TIMUR - Parino Parino; Ema Firda Happy Kurnia (ipdn, 2019)
The Effectiveness of the Trade Service Strategy in the Development of Batik Small Industries in Kediri Regency, East Java Province. Problems were observed in this paper include: how the effectiveness of the strategy of the Department of Trade in developing small batik industry in Kediri, and what are the factors that support the achievement of the effectiveness of the Department of Trade strategy in the development of small batik industry in Kediri. This observation aims to identify and analyze the effectiveness of the strategy of the Department of Trade to develop small industries batik. Observation method used is descriptive qualitative, while the data collection techniques are participatory observation, semi-structured interviews, and documentation. Data were analyzed using triangulation. The activity in the analysis of the data are data reduction, data display, and withdrawal of the conclusion. Strategies undertaken by the Department of Trade Kediri in developing small industries batik namely: infrastructure development, development, marketing, and human resource development. The observation is based on the size of the effectiveness of the measures of effectiveness in Streers Duncan, implementation strategies Department of Trade in the development of small industries batik based on indicators of goal achievement, integration, and adaptation have not been effective. Factors that hinder the achievement of the effectiveness of the strategy of the Department of Trade in the development of small industrial batik namely: lack of funding, lack of mastery of technology by batik entrepreneurs, lack of manpower batik, raw materials are still being sought from outside Kediri, means Sanri unfavorable, lack of socialization of the Department of Trade about programs that will be conducted, and low skills in batik Kediri Regency society. Keywords: effectiveness, strategy, small industry